2017
DOI: 10.1007/s13139-017-0481-x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Decline of Striatal Subregional [18F]FP-CIT Uptake in Parkinson’s Disease

Abstract: The longitudinal decline of striatal [F]FP-CIT uptake in PD was nonlinear and significantly faster than that in non-PD, with a different rate of decline among the striatal subregions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…4 . Yearly DAT decline in PD patients has been estimated to be between 5 and 13% in striatal regions [ 31 , 36 , 37 ], meaning that [ 18 F]FE-PE2I PET is well suited for measuring biological DAT differences in striatal regions in a longitudinal follow-up study with a typical sample size for PET studies.
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…4 . Yearly DAT decline in PD patients has been estimated to be between 5 and 13% in striatal regions [ 31 , 36 , 37 ], meaning that [ 18 F]FE-PE2I PET is well suited for measuring biological DAT differences in striatal regions in a longitudinal follow-up study with a typical sample size for PET studies.
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…We included the remaining 33 articles (six articles reported PET studies involving 779 patients with PD and 124 controls, and 27 reported SPECT studies involving 1244 PD patients and 859 controls) in this meta‐analysis. These studies comprised cross‐sectional surveys (10 studies), case‐control studies (19 studies), and cohort studies (four studies) 17,22–26,35–61 . Figure 1 illustrates the protocol for the literature search and study selection process.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 1, the number of participants in the other five included studies met the sample size requirements for a typical molecular imaging study 67–75 . With respect to individual studies, all included studies, except one (findings in the caudate nucleus in Sung’s study 24 ), reported a significant decrease in the SUVR for 18 F‐FP‐CIT uptake in the three striatum regions (caudate nucleus, anterior putamen, and posterior putamen) in patients with PD compared to that in the controls. Moreover, the overall effect size indicated significantly decreased 18 F‐FP‐CIT uptake in the targeted cerebral regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between sample size and effect size was examined as a function of statistical power and is presented in Figure 4. Yearly DAT-decline in PD-patients has been estimated to be between 5 and 13% in striatal regions [31,36,37], meaning that [ 18 F]FE-PE2I PET is well suited for measuring biological DAT-differences in striatal regions in a longitudinal follow-up study with a typical sample size for PET studies. Representative test and retest parametric BPND images of [18F]FE-PE2I.…”
Section: Power Calculationmentioning
confidence: 99%